Amino-Acid Homopolymers Occurring in Nature - Hamano, Yoshimitsu; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Microorganisms are capable of producing a wide variety of biopolymers. Homopolymer peptides, which are made up of only a single type of amino acid, are far less ubiquitous. The only two amino-acid homopolymers known to occur in nature are presented in this volume. Poly-epsilon-L-lysine is a polycationic peptide and exhibits antimicrobial activity against a wide spectrum of microorganisms. It is both safe and biodegradable and is therefore used as a food preservative in several countries. In addition, there has been great interest in medical and other applications of poly-lysine and its derivatives. In contrast, poly-gamma-glutamic acid is an unusual anionic polypeptide. It is also water soluble, biodegradable, edible, non-toxic and non-immunogenic and can be chemically modified to introduce various drugs. These features are very useful for pharmaceutical and biomedical applications. Poly-glutamic acid is also a highly attractive as food ingredient.
Occurrence and Production of Poly-Epsilon-l-Lysine in Microorganisms -- Biochemistry and Enzymology of Poly-Epsilon-l-Lysine Biosynthesis -- Biochemistry and Enzymology of Poly-Epsilon-l-Lysine Degradation -- Biotechnological Production of Poly-Epsilon-l-Lysine for Food and Medical Applications -- Occurrence and Biosynthetic Mechanism of Poly-Gamma-Glutamic Acid -- Enzymatic Degradation of Poly-Gamma-Glutamic Acid -- Pharmaceutical and Medical Applications of Poly-Gamma-Glutamic Acid -- Food Applications of Poly-Gamma-Glutamic Acid.
Keywords: Life sciences; Biochemistry; Microbiology; Life Sciences; Microbiology; Biochemistry, general